Racism in psychology challenging theory, practice and institutions - Newnes, Craig (London : Routledge, 2021)
Racism in Psychology examines the history of racism in psychological theory, practice and institutions. The book offers critical reviews by scholars and practising therapists from the US, Africa, Asia, Aoteoroa New Zealand, Australia and Europe on racism on the couch and in the wider socio-historical context. The authors present a mixed experience of the success of efforts to counter racism in theory, institutions and organisations and differing views on the possibility of institutional change. Chapters discuss the experience of therapists, anti-Semitism, inter-sectionality and how psychological praxis is part of a colonialist project. The book will appeal to practising psychologists and counsellors, socially minded psychotherapists, social workers, sociologists and students of psychology, social studies and race relations.
OCLC-licensed vendor bibliographic record.
Keywords: Racism -- Psychological aspects; Race relations -- Psychological aspects; PSYCHOLOGY / Clinical Psychology; PSYCHOLOGY / Mental Health